Pengaruh Pemotongan Eksplan Dan Pemberian Beberapa Konsentrasi Air Kelapa Terhadap Pertumbuhan Dan Perkembangan Eksplan Pisang Ketan (Musa paradisiaca) Secara In Vitro - M Eriansyah; Susiyanti Susiyanti; Yuhelsa Putra (Agrologia, 2014)
The purpose of this research is to know the influence of the cutting eksplan banana (Musa paradisiaca) c.v. Ketan and the granting of several concentrations of coconut water to the growth and development of in vitro eksplans. This research was carried out in the laboratory of Biotechnology , Faculty of agriculture, University of Sultan Ageng Tirtayasa, from August 1995 to  November 2013. This study used a Randomized Complete Design (RAL) with two factors. The first factor was the cutting eksplan (b) consisting of two levels, namely eksplan without slashing eksplan (b1) and (b2) halved. The second factor was the coconut water (e), which consists of six levels, namely 0%/l (e1), 3%/l (e2), 10%/l (e3), 3%/l (e4), 20%/l (e5) and 25%/l (e6). Each treatment was repeated as many as 3 times so that there are 36 units attempted.The observation was done every day to grow the buds and time each week to the high number of variables buds, shoots as well as at the end of the observation to the independent living eksplan percentage, the percentage of contaminated eksplan, the percentage of dead eksplan and eksplan form the percentage of roots. Cutting eksplan gave no real influence in banana. Giving coconut water gives a real influence over time grow shoots, buds and high number of shoots banana. The best coconut water coconut water at concentrations of 20%/l MS media.